2014
DOI: 10.1371/journal.pone.0086063
|View full text |Cite
|
Sign up to set email alerts
|

Longer Telomeres Are Associated with Cancer Risk in MMR-Proficient Hereditary Non-Polyposis Colorectal Cancer

Abstract: Aberrant telomere length measured in blood has been associated with increased risk of several cancer types. In the field of hereditary non-polyposis colorectal cancer (CRC), and more particularly in Lynch syndrome, caused by germline mutations in the mismatch repair (MMR) genes, we recently found that cancer-affected MMR gene mutation carriers had shorter telomeres and more pronounced shortening of telomere length with age than controls and unaffected MMR gene mutation carriers. Here we evaluate blood telomere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…Our principal finding was that cases with colorectal polyps or CRC had longer bowel telomeres, independent of other risk factors. There is a controversy about the effects of telomere length on the risk of many cancers, including CRC ( Quin et al , 2014 ; Seguí et al , 2014 ), but almost all studies have measured telomere length in peripheral blood. Our finding of no correlation between telomere length in the colorectum and blood may help to explain the inconsistent results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our principal finding was that cases with colorectal polyps or CRC had longer bowel telomeres, independent of other risk factors. There is a controversy about the effects of telomere length on the risk of many cancers, including CRC ( Quin et al , 2014 ; Seguí et al , 2014 ), but almost all studies have measured telomere length in peripheral blood. Our finding of no correlation between telomere length in the colorectum and blood may help to explain the inconsistent results of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In some types of cancers, such as gastric and bladder cancer, shorter RTL in leukocytes was a risk factor of tumorigenesis, [12,13,21] while it was opposite in lung and colorectal cancer. [17,18] …”
Section: Discussionmentioning
confidence: 99%
“…Some findings showed that shorter telomere length not only increases the risk of gastric cancer, [12] but also decreases the survival rate of bladder cancer, [13] while in other epidemiologic investigates, longer telomere length was associated with the increased risk of cancers that were reported. [1418] To date, little research has investigated the relationship between telomere length and the event of hepatocarcinogenesis (from normal, CHB to HCC) to our knowledge. In this study, the changes of leukocytes telomere length in different cohorts of diseases in a southwest Han Chinese population were investigated to try to understand the relationship of RTL in different stages of hepatocarcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…After screening titles and abstracts, 20 full texts were retrieved; seven studies (with 8 data sets) [2228] were selected for inclusion in this meta-analysis. Thirteen studies [29–41] were excluded as they did not meet the inclusion criteria. Reasons for the exclusion were summarized in Additional file 2: Table S1.…”
Section: Resultsmentioning
confidence: 99%